Pengembangan Video Tutorial Pembuatan Carabikang Untuk Pembelajaran Kue Tradisional Indonesia - Fawatih, Vina Intania; Astuti, Nugrahani; Sutiadiningsih, Any; Widagdo, Andika Kuncoro (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study is a development research using the 4D Thiagarajan model development method which is carried out only up to 3 stages, namely define, design and develop. The objectives of this study are: 1) the feasibility of video tutorial media for making carabikang for traditional Indonesian cake learning; 2) students’ understanding response to video tutorial media for making carabikang for traditional Indonesian cake learning. Research data were obtained using media and material expert validation sheets. Learner response data was obtained using a questionnaire with a Likert scale and learner understanding data was obtained using cognitive tests. The results of this study showed: 1) media feasibility 92% (very feasible); material feasibility 85% (very feasible) and user feasibility 93% (very practical) 2) the results of students’ understanding responses based on cognitive tests obtained an average score of 84 (complete) and classical learning completeness of 91% with a very high category. This shows that the video tutorial for making carabikang is declared feasible, very practical, and can be used for learning traditional Indonesian cakes.